أثر التوكيدية على إصدار الأحكام الأخلاقية "دراسة ميدانية على عينة من طلبة كليّتي التربية والاقتصاد في جامعة تشرين" (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2016)
يهدف البحث الحالي إلى دراسة أثر توكيد الذات على إصدار الأحكام الأخلاقية لدى عينة من طلبة كليتي التربية والاقتصاد, حيث تلخصت مشكلة البحث بالسؤال الآتي: ما أثر التوكيدية على إصدار الأحكام الأخلاقية لدى عينة من طلبة كليّتي التربية والاقتصاد في جامعة تشرين. بلغ حجم عينة البحث (240) طالباً وطالبة من طلبة كليّتي التربية والاقتصاد في جامعة تشرين بمحافظة اللاذقية. تم استخدام مقياس الحكم الأخلاقي, ومقياس التوكيدية, للحصول على البيانات من أفراد العينة, كما تم استخدام مجموعة من الأساليب الإحصائية (معامــــل ألفا كرونباخ, واختبار الدلالــــة T-test لقياس الفروق بين المجموعات), وبعد التطبيق خلص البحث للنتائج الآتية: • عدم وجود فروق بين متوسطات إجابات طلاب كلية التربية ومتوسطات إجابات طلاب الاقتصاد على مقياسي الحكم الأخلاقي والتوكيدية.• عدم وجود فروق بين متوسطات إجابات الطلاب على مقياسي الحكم الأخلاقي ومقياس التوكيدية تعزى لمتغير الجنس (ذكور, إناث), والكلية. وبالنظر إلى النتائج المستخلصة تم تقديم عدد من المقترحات أهمها العمل من قبل الأهل والمدرسين ومؤسسات المجتمع المدني على وضع برامج تساهم في تعريف الشباب بذواتهم وتشجيعهم على توكيدها من خلال تعزيز الثقة بالنفس وإبداء الرأي دون الإساءة للآخر. This research aims to study the effect of Assertiveness on producing moral judgment for a sample of educational and economic students in Tishreen university. The research problem was represented in the following main question :what is the effect of Assertiveness on producing moral judgment for a sample of educational and economic students in Tishreen university? The sample of this research was consisted of (240) students (male and female) students of educational and economic students in Tishreen university in Lattakia. A combination of scale were used in this research including a scale of Assertiveness, and a scale of Moral Judgment. Researcher used statistical methods as following: (T test, Alfa test). The research out com revealed the following: The results indicated no statistically significant differences between the mean scores of the educational and economic students on a scale of the Assertiveness and a scale of Judgment, the results indicated no statistically significant differences between the mean scores of students due to the variables of gender (sex) and college. Looking at the out results a number of suggestions have given, the more important were: working from the parents, teachers and civil community instigations to put programs help in  youth selves definition and enhancing to further  the self due to  self- supporting, showing opinions without hurting others, which reflex on producing Moral judgments.